THE EFFECT OF APPLICATION OF RICE DISHWATER AND MANURE AS ORGANIC FERTILIZER TO THE GROWTH OF MUSTARD (Brassica Juncea L.) - amalia noviyanty; Chitra Anggriani Salingkat (AGROLAND: The Agricultural Sciences Journal, 2018)
One of the recommended concepts of organic agriculture is the use of organic fertilizers and minimizing the use of inorganic fertilizers in farming activities or crop cultivation. Manure is one of the organic fertilizers that are often used as fertilizer, one of which is goat manure. In addition, there are several types of household waste that can be used as liquid organic fertilizers such as the waste rice washing water that can be applied to plants. The research objective were to determine the effect of giving rice washing water waste and manure to the growth and yield of mustard plants. This research was conducted from February to April 2017. This study used a randomized block design with two factors consisting of 16 treatments and repeated three times. The first factor isto control rice washing waterwith a concentration of 10, 20 and 30 ml/liter of water and the second factor is manure consisting of control, manure 5, 10 and 15 grams. This study uses quantitative data analysis techniques. Analysis of quantitative descriptive data used is plant height and number of leaves.Observation results of plant height showed that the highest average of plant height was experienced by 20 ml/liter rice washing water and 15 goat manure treatment. Likewise, the average number of leaves of mustard plants was not significantly different from the treatment of rice washing water, but the number of leaves in mustard plants was not significant. The results showed there were no significant interactions between the concentration of rice washing water and manure doses on growth and yield of mustard greens The rice washing water did not have a significant effect on plant height and number of leaves. The difference in the results of this study was thought to be caused by differences in the types of rice used.